Phenolic Content, Antioxidant Activity and Quality Characteristics of Hulled Wheats Originating from Türkiye - Fatma Ruveyda Alkan; Buket Çetiner; Hüseyin Akşit; Samed Şimşek (Turkish Journal of Agriculture: Food Science and Technology, 2025)
This study investigated selected quality and functional characteristics of 17 hulled wheat accessions (Triticum monococcum and Triticum dicoccum) preserved in the Türkiye Seed Gene Bank, along using four modern wheat cultivars (Triticum aestivum L. and Triticum durum Desf.). The samples were evaluated regarding grain color parameters (L*, a*, b*), thousand kernel weight, and protein content. Furthermore, total phenolic content (TPC) and antioxidant activities were were analyzed using DPPH and FRAP assays. The differences between samples were statistically significant in terms of DPPH activity and protein content. Species-wise comparison demonstrated that T. monococcum and T. dicoccum had the highest average protein levels. The highest DPPH antioxidant activity was recorded in T. monococcum sample no. 10 (859.67 µg mL⁻¹), while the lowest was in sample no. 2 (532.58 µg mL⁻¹) of the same species. Significant variation was found across the samples for L*, a*, b* color values, Chroma (C), Hue angle (h°), thousand kernel weight, total phenolic content, and FRAP antioxidant capacity. The highest TPC was detected in T. dicoccum sample no. 17 (11.23 mg GAE g⁻¹), and the highest FRAP reducing power was found in sample no. 14 of the same species (22.10 mg TE g⁻¹). These findings demonstrate notable diversity among hulled wheats regarding the evaluated traits and suggest their potential as valuable genetic resources for wheat breeding programs.